Engagement and attrition in digital mental health: current challenges and potential solutions - Katharine A. Smith; Thomas Ward; Sinéad Lambe; Edoardo G. Ostinelli; Charlotte Blease; Thomas Gant; Stefan M. Gold; Emily A. Holmes; Ivana Paccoud; Anastasia Vinnikova; Jochen Klucken; Peter J. Uhlhaas; et al. (npj Digital Medicine)
Abstract In digital mental health engagement rates are consistently low, which may limit its effects. Using an international multidisciplinary consensus method, including lived experience expertise and a systematic review, we identified three key challenges: (i) lack of agreed metrics for engagement; (ii) lack of evidence on how better engagement improves outcomes; (iii) lack of standards for user involvement. Three potential solutions encompassed: (i) standardisation of frameworks for reporting engagement metrics and optimal doses of digital tools, (ii) measuring engagement with more precise reporting of outcomes, including potential harms; (iii) defining standards of user involvement (including appropriate diversity, and clinician as well as user input). Digital interventions have real potential in meeting the shortfall in service provision for mental health, but this will require focus on high quality research studies of the underlying mechanisms of engagement and optimal outcomes. Our findings identify and highlight the next best steps in this process.